Optimising Wind Energy Capture: An IoT-Based Approach to Height Adjustment in Roadside Wind Turbines - Abdul Rahman, Mat; Faizatul Fitri, Bostamam (IEEE, 2026)
This study aims to develop an Internet of Things (IoT)-based Automated Height Adjusting Roadside Wind Turbine to enhance the efficiency of wind energy capture. The primary research objective is to investigate the relationship between varying wind speeds and the optimal height settings for roadside wind turbines. The study employs a scaled-down version of a roadside wind turbine, simulating real-world conditions to gather real-time data on wind speed, turbine height, and power generation. Through iterative testing and data analysis, the project evaluates the performance of the wind turbine at different height adjustments in response to fluctuating wind conditions. Preliminary results indicate a significant correlation between wind speed and the optimal height settings for maximising energy capture. The data collected from the scaled-down turbine provides insights that can be extrapolated to predict the performance of full-scale roadside wind turbines, suggesting a potential framework for future implementations. This research contributes to the field of renewable energy by integrating IoT technology with wind turbine design, offering a novel approach to optimise energy capture in roadside applications. The findings have implications for the development of more efficient wind energy solutions, paving the way for enhanced sustainability in urban environments.